Financialisation, green investments, technological innovation, environmental governance and resource dependence impacts on environmental quality: evidence from BRICS economies - Fortune Ganda (Cogent Economics & Finance)
The BRICS economies, despite their swift economic expansion, confront escalating environmental difficulties. This study examines the complex relationship of financialisation, green investments, technological innovation, environmental governance, and resource reliance on environmental quality in these nations. This study uses the Methods of Moments Quantile Regression (MMQR) technique and the Dumitrescu-Hurlin (DH) panel causality test to analyze the intricate mechanisms affecting environmental deterioration within the BRICS framework from 2000 to 2019. The study shows a significant negative association between carbon emissions and financial development in financial institutions and markets. Green investments, environmental governance, economic growth, natural resource rents, material footprint, and technological innovation significantly positively affect emissions. FDI's environmental impact increases in developed BRICS countries. The study reveals a reciprocal relationship between carbon emissions and financial development, economic growth, natural resource revenues, material footprint, and green investments, highlighting a one-way impact on financial markets and environmental governance. The research also suggests unidirectional connections between financial market development and carbon emissions, and technical innovations and emissions, but no substantiated association exists between emissions and foreign direct investment.